[The clinical relevancy of microbiology in chronic wounds]. - Pina E (Nursing: Revista de Formacao Continua em Enfermagem)
The clinical relevance of wound microbiology and its contribution to delayed healing are subject of some controversy. Sampling methods, issues of quantitative versus qualitative analysis and limitations of cultural methods in the diagnosis of infection in chronic wounds are discussed The author concludes that diagnosis of infection must be based on clinical signs and symptoms and routine microbiological assessment is not indicated In order to make the best use of information obtained by microbiological studies, these should be reserved for specific, well defined situations.